2021
DOI: 10.3390/catal11111258
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Pd Nanoparticles for Sustainable and Environmentally Benign Processes

Abstract: Among transition metal nanoparticles, palladium nanoparticles (PdNPs) are recognized for their high catalytic activity in a wide range of organic transformations that are of academic and industrial importance. The increased interest in environmental issues has led to the development of various green approaches for the preparation of efficient, low-cost and environmentally sustainable Pd-nanocatalysts. Environmentally friendly solvents, non-toxic reducing reagents, biodegradable capping and stabilizing agents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 182 publications
0
17
0
Order By: Relevance
“…In recent times, Pd nanomaterials have attracted considerable interest in healthcare, as discussed earlier in the introduction also. [1][2][3][4][5] A few reports on the application of Pd nanomaterials in anticancer treatment could also be seen in the literature. 91,92 Nonetheless, in the present work, an attempt was carried out to explore the anticancer efficacy of Pd nanomaterials and examine the effect of their morphology on the same.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
See 3 more Smart Citations
“…In recent times, Pd nanomaterials have attracted considerable interest in healthcare, as discussed earlier in the introduction also. [1][2][3][4][5] A few reports on the application of Pd nanomaterials in anticancer treatment could also be seen in the literature. 91,92 Nonetheless, in the present work, an attempt was carried out to explore the anticancer efficacy of Pd nanomaterials and examine the effect of their morphology on the same.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…Particularly, in the last two decades, researchers have demonstrated tremendous improvement in the properties and efficacies of Pd nanoparticles (NPs) being evaluated for various applications primarily related to the above-mentioned domains. [1][2][3][4][5][6][7] In addition to these areas, Pd NPs have recently generated considerable interest in healthcare due to their antimicrobial, wound-healing, antioxidant, and anticancer properties. 8,9 Nonetheless, a significant portion of these findings can be attributed to the development of novel methodologies for the synthesis of Pd NPs, which enable precise control over their characteristics, such as size, shape, surface properties, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies revealed that bio-synthesized palladium nanoparticles (Pd NPs) present antioxidant, anticancer, antimicrobial, antiproliferative, and photothermal activities while being biocompatible and less toxic than their chemically-synthesized counterparts [118]. Thus, they hold great promise in developing novel and improved cancer therapies, being already evaluated against several cancer cell lines (e.g., lung cancer [48], breast cancer [119], ovarian cancer [120], cervical cancer [121], and colorectal adenocarcinoma [121]).…”
Section: Other Metal-based Nanomaterialsmentioning
confidence: 99%